GAMBARAN JENIS NAPZA DALAM URINE DAN DURASI REHABILITASI PADA PASIEN NAPZA DI RS DR RADJIMAN WEDIODININGRAT LAWANG - Cindy Tanggu Humba; Previta Zeizar; Erni Yohani Mahtuti (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Abstract NAPZA (Narcotics, Psychotropics, and other Addictive Substances) are substances that affect the central nervous system and can cause physical, psychological, and social disorders due to dependence. Drug abuse has become a serious problem in both health and social aspects because it has a broad impact on the quality of life of individuals, families, and communities. Rehabilitation efforts are an important step in restoring patients’ conditions from the effects of dependence. This study aims to describe the types of NAPZA detected in the urine of rehabilitation patients at Dr. Radjiman Wediodiningrat Hospital, Lawang, during the period of January–July 2025. The study used a descriptive quantitative design with a total sample of 30 rehabilitation patients obtained through secondary data. Urine examinations were conducted using a strip test covering five parameters, namely amphetamine (AMP), methamphetamine (MET), benzodiazepine (BZO), tetrahydrocannabinol (THC), and morphine (MOP). The results showed that the most frequently detected substances were stimulants, with AMP and MET found in 6 respondents each (20%). THC was detected in 1 respondent (3.3%), while BZO and MOP were not found in any sample (100% negative). In conclusion, the pattern of NAPZA abuse among rehabilitation patients was dominated by stimulants (AMP and MET), cannabis (THC) use was relatively low, and there was no abuse of BZO or MOP.